Cellulose / plastic composite aerogel and preparation method thereof

By combining plastic with cellulose aerogel to form a composite aerogel, the problem of poor mechanical properties of cellulose aerogel is solved, and the effect of high strength, high toughness and waste plastic resource utilization is achieved.

CN119859308APending Publication Date: 2025-04-22CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311365488.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Cellulose aerogel has poor mechanical properties, low strength, poor toughness and easy to break.

Method used

By dissolving the plastic in an organic solvent, a homogeneous solution is formed and added to the cellulose aerogel for aging, and finally a cellulose/plastic composite aerogel is obtained by freezing and drying.

Benefits of technology

It improves the mechanical strength and toughness of cellulose/plastic composite aerogels, solves the problem of poor mechanical properties of traditional cellulose aerogels, and provides a resource utilization method for waste plastics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of solid waste plastic recycling, in particular to cellulose / plastic composite aerogel and a preparation method thereof. The method comprises the following steps: (1) dissolving plastic in an organic solvent to obtain a homogeneous solution; (2) adding the homogeneous solution into cellulose aerogel, and then performing aging treatment to obtain an aged product; and (3) freezing the aging product to obtain the cellulose / plastic composite aerogel. According to the preparation method of the cellulose / plastic composite aerogel, the homogeneous solution containing the plastic is dropwise added into the cellulose aerogel, the toughness of the plastic can be utilized, the problem that traditional cellulose aerogel is poor in mechanical property can be solved, and therefore the cellulose / plastic composite aerogel which is high in mechanical strength, good in toughness and not prone to being broken can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid waste plastic resource recovery, and in particular to a cellulose / plastic composite aerogel and a preparation method thereof. Background Art

[0002] Cellulose aerogel is the third generation of aerogel that has emerged after inorganic aerogel and organic aerogel. Compared with traditional aerogel, cellulose aerogel has many advantages: first, cellulose is one of the most abundant natural polymers in nature, with a wide range of raw materials, large reserves and easy access; second, cellulose aerogel has the characteristics of traditional aerogels, and also incorporates the excellent properties of cellulose itself, such as biocompatibility and degradability, and has good application prospects in the pharmaceutical industry, cosmetics, etc.; in addition, cellulose contains many active hydroxyl groups, and cross-linking agents do not need to be used in the preparation of aerogels. Only through the physical cross-linking of intramolecular and intermolecular hydrogen bonds at the ultrastructural level, a three-dimensional porous structure can be formed, making the preparation process of aerogels quite simple.

[0003] However, cellulose aerogel also has its own defects: since many hydroxyl groups on cellulose cannot form effective hydrogen bonds, the mechanical properties of cellulose aerogel are poor, such as low strength, poor toughness, and easy breakage.

[0004] In CN106009031B, cellulose is dissolved in a mixture of NaOH, polyvinyl alcohol and water, and then heated, frozen, regenerated in acid solution and dried to obtain a high-strength cellulose aerogel, whose elastic modulus and toughness reach 1.03MPa and 245kJ / m respectively. 3 . CN103709435B discloses a method for preparing a lightweight and high-strength cellulose aerogel, which comprises preparing a cellulose solution, and then freezing and thawing the cellulose solution for 1 to 100 times to obtain a cyclically treated cellulose solution, and then adding the cyclically treated cellulose solution to an acidic solution for gelation, displacement and drying to obtain a lightweight and high-strength cellulose aerogel. The maximum load of the cellulose aerogel prepared by this method can reach 50N-200N, but both methods require the additional addition of the reactant polyvinyl alcohol and require acid-base reaction conditions, and the process flow is relatively complicated.

[0005] CN103012835A discloses a method for preparing a cellulose / polyurethane composite aerogel, which comprises the following steps: step 1, first dissolving cellulose with a cellulose green dissolving system, and then preparing a cellulose wet gel; step 2, performing solvent exchange on the cellulose wet gel obtained in step 1 to obtain a cellulose organic wet gel containing an organic solvent; step 3, dissolving an isocyanate resin and a catalyst in an organic solvent; step 4, immersing the cellulose wet gel obtained in step 2 into the solution described in step 3 to obtain a cellulose / polyurethane composite wet gel; and step 5, drying the cellulose / polyurethane composite wet gel obtained in step 4 to obtain a cellulose / polyurethane composite aerogel. Although the cellulose / polyurethane composite aerogel prepared by this method has excellent mechanical properties, it also has the defects of complex preparation processes and long cycles such as solvent exchange.

[0006] Therefore, there is an urgent need to provide a method that is simple to operate and can prepare cellulose aerogels with good mechanical properties. Summary of the invention

[0007] The purpose of the present invention is to solve the problems of low strength, poor toughness and easy breakage of cellulose aerogel, and to provide a cellulose / plastic composite aerogel and a preparation method thereof.

[0008] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a cellulose / plastic composite aerogel, wherein the method comprises the following steps:

[0009] (1) dissolving the plastic in an organic solvent to obtain a homogeneous solution;

[0010] (2) adding the homogeneous solution to the cellulose aerogel, and then performing an aging treatment to obtain an aged product;

[0011] (3) The aged product is subjected to freezing treatment to obtain a cellulose / plastic composite aerogel.

[0012] The second aspect of the present invention provides a cellulose / plastic composite aerogel prepared by the method described in the first aspect of the present invention.

[0013] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:

[0014] 1) The preparation method of the cellulose / plastic composite aerogel provided in the present invention can solve the problem of poor mechanical properties of traditional cellulose aerogel by dropping a homogeneous solution containing plastic into the cellulose aerogel, utilizing the toughness of the plastic, thereby obtaining a cellulose / plastic composite aerogel with high mechanical strength, good toughness and not easy to break;

[0015] 2) The preparation method of the cellulose / plastic composite aerogel provided in the present invention can use waste plastics to prepare cellulose / plastic composite aerogels, which provides a new way for the high-value resource utilization of waste plastics, is of great significance for promoting the development of aerogel materials, alleviating the white crisis, and improving the natural environment, and has good environmental benefits, social benefits and economic benefits;

[0016] 3) The cellulose / plastic composite aerogel provided in the present invention has high mechanical strength and good toughness, beneficial performance, and broad application prospects. DETAILED DESCRIPTION

[0017] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0018] A first aspect of the present invention provides a method for preparing a cellulose / plastic composite aerogel, wherein the method comprises the following steps:

[0019] (1) dissolving the plastic in an organic solvent to obtain a homogeneous solution;

[0020] (2) adding the homogeneous solution to the cellulose aerogel, and then performing an aging treatment to obtain an aged product;

[0021] (3) The aged product is subjected to freezing and drying treatment to obtain a cellulose / plastic composite aerogel.

[0022] In step (1):

[0023] In one embodiment of the present invention, the plastic is selected from one or more of polyethylene (PE), polypropylene (PP), polystyrene (PS), polyvinyl chloride (PVC), polyurethane (PU), polyvinylidene chloride (PVDC), polyvinyl alcohol (PVA), and polyethylene terephthalate (PET).

[0024] The plastic in the present invention can be either waste plastic or new plastic. In order to reduce the production cost of cellulose / plastic composite aerogel and realize the resource utilization of waste plastic, it is preferred to use waste plastic to prepare cellulose / plastic composite aerogel. In order to increase the dissolution rate of plastic, the plastic can be crushed before dissolving it with an organic solvent. If it is waste plastic, the waste plastic can also be cleaned and dried to remove mechanical impurities in the waste plastic.

[0025] In one embodiment of the present invention, the organic solvent is selected from one or more of water, xylene, tetralin, decalin, hexadecane, dimethyl sulfoxide, cyclohexanone, tetrahydrofuran, methyl ethyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, trifluoroacetic acid, hexafluoroisopropanol, and o-chlorophenol.

[0026] In one embodiment of the present invention, the plastic is polyethylene and / or polypropylene, and the organic solvent is one or more of xylene, tetralin, decalin, and hexadecane, preferably hexadecane.

[0027] In one embodiment of the present invention, the plastic is polystyrene, and the organic solvent is one or more of cyclohexanone, xylene, tetralin, and decalin, preferably cyclohexanone.

[0028] In one embodiment of the present invention, the plastic is polyvinyl chloride, and the organic solvent is one or more of dimethyl sulfoxide, cyclohexanone, tetrahydrofuran, methyl ethyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone, preferably dimethyl sulfoxide.

[0029] In one embodiment of the present invention, the plastic is polyurethane and / or polyvinylidene chloride, and the organic solvent is one or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone, preferably dimethyl sulfoxide.

[0030] In one embodiment of the present invention, the plastic is polyvinyl alcohol, and the organic solvent is water and / or N,N-dimethylformamide, preferably N,N-dimethylformamide.

[0031] In one embodiment of the present invention, the plastic is polyethylene terephthalate, and the organic solvent is one or more of trifluoroacetic acid, hexafluoroisopropanol, and o-chlorophenol, preferably hexafluoroisopropanol.

[0032] In one embodiment of the present invention, the mass ratio of the plastic to the organic solvent is 1:10-200, preferably 1:20-100.

[0033] Among them, in the present invention, limiting the masses of the plastic and the organic solvent within the above range can ensure that the plastic can be fully dissolved in the organic solvent to obtain a homogeneous solution.

[0034] In one embodiment of the present invention, the dissolution operating conditions include: a dissolution temperature of 40-140°C, preferably 50-70°C; and a dissolution time of 15-120 min, preferably 30-60 min.

[0035] In step (2):

[0036] In a preferred embodiment of the present invention, the present invention does not specifically limit the cellulose aerogel, and any cellulose aerogel that can be synthesized according to a known method (e.g., a sol-gel method) or that can be purchased from the market can be used in the present invention, including but not limited to natural cellulose aerogel, regenerated cellulose aerogel, and cellulose derivative aerogel.

[0037] In a preferred embodiment of the present invention, the adding method is selected from equal volume immersion and / or dripping, preferably dripping.

[0038] In a preferred embodiment of the present invention, the equal volume impregnation operation comprises: immersing the cellulose aerogel in a homogeneous solution at a temperature of 25-50° C., preferably 30-40° C., and for a time of 20-80 min, preferably 40-60 min.

[0039] In a preferred embodiment of the present invention, the dropping speed is 30-200 d(drops) / min, preferably 60-100 d(drops) / min.

[0040] Among them, in the present invention, the homogeneous solution can be evenly dispersed in the cellulose aerogel by dripping, which is helpful to improve the mechanical properties of the cellulose / plastic composite aerogel.

[0041] In a preferred embodiment of the present invention, the dropping temperature of the homogeneous solution is 25-50°C, preferably 30-40°C.

[0042] Among them, in the present invention, when the dropping temperature is low, the viscosity of the homogeneous solution is large, which easily leads to uneven distribution of the homogeneous solution in the cellulose aerogel; when the dropping temperature is low, the cellulose aerogel skeleton will be deformed, which easily leads to poor stability of the cellulose / plastic composite aerogel. When the homogeneous solution is dropped at the above-defined temperature, the mechanical properties of the prepared cellulose / plastic composite aerogel can be optimized.

[0043] In one embodiment of the present invention, the homogeneous solution is added until the homogeneous solution remains on the surface of the cellulose aerogel and no longer penetrates into the cellulose aerogel.

[0044] In the present invention, after the homogeneous solution contacts the cellulose aerogel, the homogeneous solution will penetrate into the cellulose aerogel and be absorbed by the cellulose aerogel. When the cellulose aerogel reaches saturation, it can be observed with the naked eye that the homogeneous solution stays on the surface of the cellulose aerogel and no longer continues to penetrate downward. At this time, the addition of the homogeneous solution can be stopped.

[0045] In one embodiment of the present invention, the operating conditions of the aging treatment include: an aging temperature of 25-50°C, preferably 30-40°C; an aging time of 4-48h, preferably 24-36h.

[0046] Among them, in the present invention, the formation of the three-dimensional network structure of the cellulose / plastic composite aerogel can be promoted through aging, and the stability of the three-dimensional network structure of the cellulose / plastic composite aerogel can be improved.

[0047] In one embodiment of the present invention, the step (2) further comprises performing an ultrasonic treatment before the aging treatment.

[0048] Among them, in the present invention, ultrasound treatment is first performed and then aging treatment is performed, which can further improve the mechanical properties of the cellulose / plastic composite aerogel.

[0049] In one embodiment of the present invention, the operating conditions of the ultrasonic treatment include: ultrasonic power of 200-1000w, preferably 500-700w; ultrasonic time of 10-50min, preferably 20-40min.

[0050] In step (3):

[0051] In one embodiment of the present invention, the operating conditions of the freezing treatment include: the freezing treatment temperature is -90°C to -60°C, preferably -80°C to -70°C; the freezing treatment time is 12-60h, preferably 24-48h.

[0052] In one embodiment of the present invention, the drying is selected from one or more of freeze drying, supercritical carbon dioxide drying, and vacuum freeze drying.

[0053] The second aspect of the present invention provides a cellulose / plastic composite aerogel prepared by the method described in the first aspect of the present invention.

[0054] Among them, the cellulose / plastic composite aerogel provided in the present invention has high mechanical strength, good toughness, and is not easy to break. It can be widely used in the fields of sound insulation and noise reduction, heat insulation, cushioning material packaging, etc.

[0055] The present invention will be described in detail below through examples.

[0056] Preparation method of cellulose aerogel in the embodiment and comparative example:

[0057] 1 g of carboxymethyl cellulose was added to 99 g of deionized water and stirred at 50°C until completely dissolved to obtain a homogeneous cellulose solution; 0.1 g of polyethylene glycol diglycidyl ether was added to the homogeneous cellulose solution, and the solution was stirred at 1000 rpm for 20 min, and then the bubbles were removed by ultrasonic treatment at a power of 600 W for 30 min, and then the solution was pre-frozen at -30°C for 24 h, and then vacuum freeze-dried at -196°C for 48 h to obtain a carboxymethyl cellulose aerogel.

[0058] Among them, polyethylene glycol diglycidyl ether was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., product model P134831; carboxymethyl cellulose was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., product model C104985.

[0059] Example 1

[0060] (1) adding waste polyvinyl chloride plastic into dimethyl sulfoxide, stirring at 60° C. for 40 minutes, until the waste polyvinyl chloride plastic is fully dissolved in the dimethyl sulfoxide to obtain a homogeneous solution; wherein the mass ratio of the waste polyvinyl chloride to the dimethyl sulfoxide is 1:50;

[0061] (2) cooling the homogeneous solution to 30°C, and dripping it onto the carboxymethyl cellulose aerogel at a rate of 80 d / min until the dripping droplets stay on the surface of the carboxymethyl cellulose aerogel and no longer penetrate downward; then, ultrasonicating the solution with a power of 600 W for 30 min, and then aging the solution at 30°C for 24 h to obtain an aged product;

[0062] (3) The aged product was pre-frozen at -60°C for 12 h and then vacuum freeze-dried at -196°C for 48 h to obtain a cellulose / plastic composite aerogel.

[0063] Example 2

[0064] (1) adding waste polyethylene to hexadecane and stirring at 130° C. for 40 minutes to fully dissolve the waste polyethylene in the hexadecane to obtain a homogeneous solution; wherein the mass ratio of the waste polyethylene to the hexadecane is 1:100;

[0065] (2) cooling the homogeneous solution to 40°C, and dripping it onto the carboxymethyl cellulose aerogel at a rate of 60 d / min until the dripping droplets stay on the surface of the carboxymethyl cellulose aerogel and no longer penetrate downward; then, ultrasonicating the solution with a power of 600 W for 30 min, and then aging the solution at 30°C for 24 h to obtain an aged product;

[0066] (3) The aged product was pre-frozen at -60°C for 12 h and then vacuum freeze-dried at -196°C for 48 h to obtain a cellulose / plastic composite aerogel.

[0067] Example 3

[0068] (1) adding waste polystyrene to cyclohexanone and stirring at 60° C. for 40 minutes to fully dissolve the waste polystyrene in the cyclohexanone to obtain a homogeneous solution; wherein the mass ratio of the waste polystyrene to the cyclohexanone is 1:70;

[0069] (2) cooling the homogeneous solution to 35°C, and dripping it onto the carboxymethyl cellulose aerogel at a rate of 100 d / min until the dripping droplets stay on the surface of the carboxymethyl cellulose aerogel and no longer penetrate downward; then, ultrasonicating the solution with a power of 600 W for 30 min, and then aging the solution at 30°C for 24 h to obtain an aged product;

[0070] (3) The aged product was pre-frozen at -60°C for 12 h and then vacuum freeze-dried at -196°C for 48 h to obtain a cellulose / plastic composite aerogel.

[0071] Example 4

[0072] (1) adding waste polyvinylidene chloride to dimethyl sulfoxide, stirring at 80° C. for 40 minutes, so that the waste polyvinylidene chloride is fully dissolved in the dimethyl sulfoxide to obtain a homogeneous solution; wherein the mass ratio of the waste polyvinylidene chloride to the dimethyl sulfoxide is 1:120;

[0073] (2) cooling the homogeneous solution to 40°C and dripping it onto the carboxymethyl cellulose aerogel at a rate of 80 d / min until the dripping droplets stay on the surface of the carboxymethyl cellulose aerogel and no longer penetrate downward; then, ultrasonicating the solution with a power of 600 W for 30 min, and then aging the solution at 30°C for 24 h to obtain an aged product;

[0074] (3) The aged product was pre-frozen at -60°C for 12 h and then vacuum freeze-dried at -196°C for 48 h to obtain a cellulose / plastic composite aerogel.

[0075] Example 5

[0076] (1) adding waste polyvinyl alcohol to N,N-dimethylformamide, stirring at 100° C. for 60 minutes, so that the waste polyvinyl alcohol is fully dissolved in the N,N-dimethylformamide to obtain a homogeneous solution; wherein the mass ratio of the waste polyvinyl alcohol to the N,N-dimethylformamide is 1:100;

[0077] (2) cooling the homogeneous solution to 40°C, and dripping it onto the carboxymethyl cellulose aerogel at a rate of 40 d / min until the dripping droplets stay on the surface of the carboxymethyl cellulose aerogel and no longer penetrate downward; then, ultrasonicating the solution with a power of 600 W for 30 min, and then aging the solution at 30°C for 24 h to obtain an aged product;

[0078] (3) The aged product was pre-frozen at -60°C for 12 h and then vacuum freeze-dried at -196°C for 48 h to obtain a cellulose / plastic composite aerogel.

[0079] Example 6

[0080] (1) adding waste polyethylene terephthalate to hexafluoroisopropanol, stirring at 50° C. for 40 minutes, so that the waste polyethylene terephthalate is fully dissolved in the hexafluoroisopropanol to obtain a homogeneous solution; wherein the mass ratio of the waste polyethylene terephthalate to the hexafluoroisopropanol is 1:80;

[0081] (2) cooling the homogeneous solution to 35°C, and dripping it onto the carboxymethyl cellulose aerogel at a rate of 120 d / min until the dripping droplets stay on the surface of the carboxymethyl cellulose aerogel and no longer penetrate downward; then, ultrasonicating the solution with a power of 600 W for 30 min, and then aging the solution at 30°C for 24 h to obtain an aged product;

[0082] (3) The aged product was pre-frozen at -60°C for 12 h and then vacuum freeze-dried at -196°C for 48 h to obtain a cellulose / plastic composite aerogel.

[0083] Example 7

[0084] The same as Example 1, except that in step (2): the carboxymethyl cellulose aerogel is immersed in a homogeneous solution, and is immersed in equal volume at 35°C for 50 minutes; then, ultrasonic treatment with a power of 600W is performed for 30 minutes, and then aging is performed at 30°C for 24 hours to obtain an aged product.

[0085] Example 8

[0086] The same as Example 1, except that in step (2): ultrasonic treatment is omitted.

[0087] Example 9

[0088] The same as Example 1, except that dimethyl sulfoxide is replaced by N,N-dimethylacetamide in an equal amount.

[0089] Example 10

[0090] The same as Example 1, except that the mass ratio of waste polyvinyl chloride plastic to dimethyl sulfoxide is 1:125.

[0091] Test Case

[0092] The toughness, elastic modulus and thermal conductivity of the carboxymethyl cellulose aerogel and the cellulose / plastic composite aerogel prepared in Examples 1-10 were tested, and the test results are shown in Table 1. The toughness and elastic modulus were tested using a universal mechanical testing machine, and the thermal conductivity was tested using a thermal conductivity tester.

[0093] Table 1

[0094]

[0095] Among them, by comparing the test results of Examples 1-6 and carboxymethyl cellulose aerogel, it can be seen that the present invention compounds plastic into carboxymethyl cellulose aerogel, and the prepared cellulose / plastic composite aerogel has good toughness, large elastic modulus, and is not easy to break.

[0096] By comparing Example 1 with Example 7, it can be seen that the dripping method can significantly improve the toughness of the cellulose / plastic composite aerogel compared with the equal volume impregnation. By comparing Example 1 with Example 8, it can be seen that ultrasonic treatment before aging is helpful to improve the toughness and elastic modulus of the cellulose / plastic composite aerogel.

[0097] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a cellulose / plastic composite aerogel, characterized in that: The method comprises the following steps: (1) dissolving the plastic in an organic solvent to obtain a homogeneous solution; (2) adding the homogeneous solution to the cellulose aerogel, and then performing an aging treatment to obtain an aged product; (3) The aged product is subjected to freezing and drying treatment to obtain a cellulose / plastic composite aerogel.

2. The preparation method according to claim 1, wherein The plastic is selected from one or more of polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyurethane, polyvinylidene chloride, polyvinyl alcohol, and polyethylene terephthalate; Preferably, the organic solvent is selected from one or more of water, xylene, tetralin, decalin, hexadecane, dimethyl sulfoxide, cyclohexanone, tetrahydrofuran, methyl ethyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, trifluoroacetic acid, hexafluoroisopropanol, and o-chlorophenol.

3. The preparation method according to claim 2, wherein The plastic is polyethylene and / or polypropylene, and the organic solvent is one or more of xylene, tetralin, decalin, and hexadecane, preferably hexadecane; Preferably, the plastic is polystyrene, and the organic solvent is one or more of cyclohexanone, xylene, tetralin, and decalin, preferably cyclohexanone; Preferably, the plastic is polyvinyl chloride, and the organic solvent is one or more of dimethyl sulfoxide, cyclohexanone, tetrahydrofuran, methyl ethyl ketone, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone, preferably dimethyl sulfoxide; Preferably, the plastic is polyurethane and / or polyvinylidene chloride, and the organic solvent is one or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone, preferably dimethyl sulfoxide; Preferably, the plastic is polyvinyl alcohol, and the organic solvent is water and / or N,N-dimethylformamide, preferably N,N-dimethylformamide; Preferably, the plastic is polyethylene terephthalate, and the organic solvent is one or more of trifluoroacetic acid, hexafluoroisopropanol, and o-chlorophenol, preferably hexafluoroisopropanol.

4. The preparation method according to any one of claims 1 to 3, wherein The mass ratio of the plastic to the organic solvent is 1:10-200, preferably 1:20-100; Preferably, the dissolution operating conditions include: dissolution temperature of 40-140°C, preferably 50-70°C; dissolution time of 15-120 min, preferably 30-60 min.

5. The preparation method according to any one of claims 1 to 4, wherein: The adding method is selected from equal volume immersion and / or dripping, preferably dripping.

6. The preparation method according to claim 5, wherein: The dropping speed is 30-200 d / min, preferably 60-100 d / min; Preferably, the homogeneous solution is added at a temperature of 25-50°C, preferably 30-40°C; Preferably, the homogeneous solution is added until the homogeneous solution remains on the surface of the cellulose aerogel and no longer penetrates into the cellulose aerogel.

7. The preparation method according to any one of claims 1 to 6, wherein: The operating conditions of the aging treatment include: aging temperature of 25-50°C, preferably 30-40°C; aging time of 4-48h, preferably 24-36h.

8. The preparation method according to any one of claims 1 to 7, wherein: The step (2) further comprises performing ultrasonic treatment before the aging treatment; Preferably, the operating conditions of the ultrasonic treatment include: ultrasonic power of 200-1000w, preferably 500-700w; ultrasonic time of 10-50min, preferably 20-40min.

9. The preparation method according to any one of claims 1 to 8, wherein: The freezing treatment temperature is -90°C to -60°C, preferably -80°C to -70°C; the freezing treatment time is 12-60h, preferably 24-48h; Preferably, the drying is selected from one or more of freeze drying, supercritical carbon dioxide drying, and vacuum freeze drying.

10. A cellulose / plastic composite aerogel prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of cellulose / polyurethane composite aerogel

    CN103012835A

  • A kind of preparation method of lightweight high-strength cellulose airgel

    CN103709435B

  • A kind of method to improve the mechanical strength of cellulose aerogel

    CN106009031B